Preparation and properties of rice protein hydrolysate-xanthan gum nanocarriers - YANG Yuqi; YAN Peizhou; CHENG Yunhui; LIN Qinlu; WANG Jing; JIAO Ye (Shipin yu jixie, 2024)
Objective: To enhance the water solubility and stability of hydrophobic active substances. Methods: A nano-delivery system of rice protein hydrolysate （RPH）-xanthan gum （XG）-curcumin （Cur） was developed, wherein curcumin served as the delivery object, and the encapsulation efficiency, stability, antioxidant activity, and formation mechanism of the nanoparticles were determined and analyzed. Results: The encapsulation efficiency of RPH-XG-Cur nanoparticles reached 78.40%, with a particle size of 74.78 nm, PDI of 0.36, and Zeta potential of -27.93 mV. Remarkably, the incorporation of xanthan gum significantly improved the encapsulation performance as well as pH and ionic strength stability of the nanoparticles. Fourier infrared and fluorescence spectra analysis revealed that hydrogen bonding, electrostatic interaction, and hydrophobic interaction played crucial roles in nanoparticle formation. Conclusion: RPH-XG nanoparticles exhibit great potential as nanocarriers for delivering hydrophobic bioactive substances.